Engaging today, building tomorrow : tools to support engagement - Australia. Department of Families, Housing, Community Services and Indigenous Affairs ([Canberra : Dept. of Families, Housing, Community Services & Indigenous Affairs, 2011)
"Engaging today, building tomorrow : a framework for engaging with Aboriginal and Torres Strait Islander Australians (the Framework) is about understanding why it is important for all levels of government in Australia to engage more effectively with Aboriginal and Torres Strait Islander people. The Framework is based on the premise that constructive engagement makes a valuable contribution to the development of good social policy and the achievement of positive outcomes -- both for government and Aboriginal and Torres Strait Islander Australians."--Introduction, ... : a framework for engaging with Aboriginal and Torres Strait Islander Australians.
Cover title.
At head of title: Closing the gap.
"FaHCSIA 11520"--Back cover.
"This toolkit has been designed as a companion document to Engaging today, building tomorrow : a framework for engaging with Aboriginal and Torres Strait Islander Australians"--Introduction.
Keywords: Indigenous peoples -- Government policy -- Australia; Indigenous peoples -- Australia -- Government relations; Indigenous peoples -- Services for -- Australia; Civil service -- Customer services -- Australia; Economic sectors - Government; Government policy - Commonwealth